Adaptive Leadership in Digital HRM: Managing Digital Transformation and Fostering Innovation Culture in Organizations - T. Nurliyana Habsjah; Agung Dharmawan Buchdadi; Corry Yohana (Lembaga Riset Ilmiah, 2026)
Digital transformation has repositioned Human Resource Management (HRM) from an administrative function into a strategic, data-driven, and technology-enabled system. However, previous studies have often examined Digital HRM as a technology adoption issue, while the leadership mechanism that connects digital change management with innovation culture remains less explicit. This study systematically reviews 20 articles published between 2015 and 2024 using PRISMA-guided procedures and thematic synthesis. The analysis focuses on adaptive leadership, digital change management, Digital HRM effectiveness, digital readiness, and innovation culture. The findings show that adaptive leadership is not a peripheral condition, but a social mechanism that converts digital tools into accepted and meaningful HR practices. Adaptive leaders reduce resistance, regulate the pace of change, strengthen two-way communication, develop digital competence, and create psychologically safe conditions for experimentation. Digital HRM becomes more effective when technological readiness is accompanied by employee participation, trust, flexible structures, and ethical governance. The study contributes an integrative framework linking adaptive leadership, digital change management, Digital HRM effectiveness, and innovation culture. Practically, organizations should design HR digitalization as a socio-technical transformation supported by leadership development, digital literacy programs, feedback systems, and human-centered HR technology governance.